SARTANS AND ANGIOTENSIN CONVERTING ENZYME INHIBITORS: A DUEL BETWEEN TWO LEADERS OF PHARMACOTHERAPY OF CARDIOVASCULAR DISEASES - K. A. Gyamdzhyan; M. L. Maksimov (Столичная издательская компания, 2015)
Topical issues of cardiovascular disease pharmacotherapy influencing function of the renin-angiotensin-aldosterone system are discussed. Efficacy and safety of two major cardiovascular drug classes, angiotensin converting enzyme inhibitors and sartans, are compared. Data from evidence base of the both drug classes are presented.